Enhanced biomass production and bioelectricity generation in microalgae culture medium using electrode pairings - Mohammed Amina Lami; Suparmaniam Uganeeswary; Lam Man Kee; Lim Jun Wei; Kiew Peck Loo; Tan Inn Shi; Chin Bridgid Lai Fui; Lau Sie Yon (E3S Web of Conferences)
Microalgae-based biofuel production offers promising avenues for sustainable energy generation. However, optimizing microalgae culture conditions for enhanced biomass production and bioelectricity generation remains challenging. This study addresses this problem by investigating the efficacy of different electrode pairings immersed in a microalgae culture medium. Two electrode pairs, Al-Fe and Cu-Zn were evaluated for their impact on microalgae growth and bioelectricity production. The optimum biomass concentration obtained was 1.204 g/L of Al-Fe electrodes with a lipid content of 15.1% and bioelectricity generation of 0.36V. The results demonstrated that Al-Fe electrodes induced high biomass concentration and lipid content in microalgae culture, facilitating biodiesel production. Conversely, Cu paired with Zn electrode promoted microalgae growth with elevated bioelectricity generation with 0.95V. This research sheds light on the potential of tailored electrode pairings to optimize microalgae culture conditions for dual-purpose biofuels and bioelectricity production, contributing to the advancement of sustainable energy technologies. It was recommended, among others, that further exploration of diverse electrode pairings within microalgae cultured medium could unveil additional effective strategies for optimizing biomass production and bioelectricity generation.